Innovation environment in small Technologie-Based Companies - Fiates, Gabriela Gonçalves Silveira (2021)
Innovation has been identified as a strategy to achieve competitive advantage, particularly in contexts of change and especially for technology-based companies - TBCs. Although the adoption of innovation strategies is not easy, small companies have an organizational environment more conducive to innovation. This article examines how managers and employees of small TBCs perceive aspects of the internal environment of innovation in the organization (culture, organizational structure, personnel and infrastructure) and their suitability for the innovation process. This is a qualitative research from a multicase study on five companies located in an incubator. Data were collected through open interviews, using a semi-structured script, with one of the managers and two employees from each company. Data were analyzed from preliminary content analysis. The results showed some discrepancies between the perceptions of managers and employees about the issues investigated and their suitability for the innovation system, as well as between reality and the theoretical basis used.